Using Quality Standards in Appointing Instructors for Electronic Learning - Alsayed Abukhatwa alsayed ab khatoh (University of Science and Technology, Yemen, 2012)
Abstract                                                                   The aim of this study is to determine the Quality standards in the recruitment of academic staff for e-learning; through the analysis of the theoretical basics and previous studies related to this subject. . Standards have been identified in seven fields: • 1.      Analysis of e-learning system. • 2.      Design of e-learning Sources. • 3.     Production of e-learning sources. • 4.     Evaluation of e-learning. • 5.     Use of e-learning. • 6.     Director of e-learning. • 7.     Ethics of e-learning. Each field contains a number of standards, a total of (93) standard. Keywords: Quality standards, E-learning standards, Competencies, and academic staff skills.